Hypoventilation and hypoxia in reversal of cardiogenic shock in an infant with congenital heart disease. Issue 5 (25th August 2004) - Sacchetti, A; Wernovsky, G; Paston, C; Fernandes, M
Abstract : The case is presented of a child in cardiogenic shock in whom oxygen administration exacerbated a systemic to pulmonary shunt that caused a critical deterioration in his cardiovascular status requiring hypoventilation and restoration of baseline hypoxia for reversal.